Legal Protection of Intellectual Property Rights for Digital-Based Creative Industries in Indonesia - Shyfa N.C., Ratu; Sudiro, Amad (Lafadz Jaya Publisher, 2024)
The progression of time and advancements in technology and information have provided many benefits to human life. Technological advancement is evident in several fields, such as photography, cinematography, and design, which fall under the scope of intellectual property, particularly copyright. However, technological and digital development has also brought several global impacts that transcend national borders. Indonesia's economy has largely relied on the tourism sector which has led to the growth of the creative industries that support this sector. Advertising, as a part of the creative industries, plays an important role in society. Various strategies have been applied to compete and to excel in the business category of communication and technology services to maintain competitiveness in the digital creative communication industry of an advertising agency in Indonesia. However, these developments have made uploading someone's work common. Subconsciously, easy and practical access to the virtual world can result in copyright infringement, in which the works uploaded on digital/online platforms can be misused by irresponsible parties for personal gain. The legal regulation for intellectual property rights in Indonesia, particularly copyright, is regulated under Law Number 28 of 2014 on Copyright. As specified in Article 40 Paragraph (1) of the Copyright Law, it addresses the creations protected under its regulations. However, with the changing times and technological advancements, there has been a blur in the norms of these regulations, which need adjustments.